PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATAKAN HASIL BELAJAR MATEMATIKA PADA MATERI ALJABAR DI KELAS VII B SMP NEGERI 6 PALU - Miranti Khairani; I Nyoman Murdiana; Mulianti Mulianti (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to improve students' mathematics learning outcomes through the application of the PBL model to algebra material in class VII B of SMP Negeri 6 Palu. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each including the planning, implementation, observation, and reflection stages with 30 students as subjects. The research instruments are in the form of learning outcome tests, observation sheets of student and teacher activities, and field notes. The results of the study showed a significant increase in learning completeness, namely from 33.3% in the initial test, increasing to 56.7% in cycle I, and reaching 86.7% in cycle II. In addition, student involvement in discussions, self-confidence, and critical thinking skills also experienced positive development.